2009
DOI: 10.3109/13697130903395201
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose hormone therapy in postmenopausal women in China

Abstract: More RCTs are required to confirm efficacy and to assess the safety of low- or ultra-low-dose HT for a long-term period in a large group of postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In our previous metabolomics studies of estrogen intervention in menopausal rat models, we found that estrogen (Nilestriol) could increase urine and serum lactate levels, which could increase the risk of breast cancer (Cheng, 1993;Liu, Huang, Xiao, Yang, & Dong, 2014b;Liu et al, 2014aLiu et al, , 2014cZang, Shi, & Speroff, 2010). Thus, it is necessary to investigate other effective substitute therapies.…”
Section: Introductionmentioning
confidence: 93%
“…In our previous metabolomics studies of estrogen intervention in menopausal rat models, we found that estrogen (Nilestriol) could increase urine and serum lactate levels, which could increase the risk of breast cancer (Cheng, 1993;Liu, Huang, Xiao, Yang, & Dong, 2014b;Liu et al, 2014aLiu et al, , 2014cZang, Shi, & Speroff, 2010). Thus, it is necessary to investigate other effective substitute therapies.…”
Section: Introductionmentioning
confidence: 93%
“…15 Nylestriol with adequate calcium and vitamin D intake could increase BMD at the lumbar spine, neck, and hip and decrease bone turnover markers in postmenopausal women. 16 To the best of authors' knowledge, there have been no previous studies on the protective effect of the combination of simvastatin and nylestriol. The purpose of this study was to compare the effects of simvastatin and combination of simvastatin and nylestriol on bone metabolism in ovariectomized (OVX) rats, thus further clarifying the efficacy of statins and combination therapy for the treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 98%
“…The most prescribed oral dose of CEE (0.625 mg) leads to supraphysiologic plasma levels of estrogen in both postmenopausal women (Sarrel et al, 1998) and animal models (Costa et al, 2015), which may increase estrogenassociated side effects and contribute to the prothrombotic effects associated with HT. For that reason, there is increasing interest in applying lower-doses of HT in postmenopausal women (Gambacciani et al, 2003a;Peeyananjarassri and Baber, 2005;Zang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%